Artificial Intelligence in Education c - Biswas, Gautam; Bull, Susan; Kay, Judy.; Mitrovic, Antonija; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 15th International Conference on Artificial Intelligence in Education, AIED 2011, held in Auckland, New Zealand in June/July 2011. The 49 revised full papers presented together with three invited talks and extended abstracts of poster presentations, young researchers contributions and interactive systems reports and workshop reports were carefully reviewed and selected from a total of 193 submissions. The papers report on technical advances in and cross-fertilization of approaches and ideas from the many topical areas that make up this highly interdisciplinary field of research and development including artificial intelligence, agent technology, computer science, cognitive and learning sciences, education, educational technology, game design, psychology, philosophy, sociology, anthropology and linguistics.
Keywords: Computer science; Information systems; Artificial intelligence; Education; Education -- Psychology; Computer Science; Artificial Intelligence (incl. Robotics).; Computers and Education; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Educational Technology; Pedagogic Psychology